Penghentian Kebijakan National Security Entry Exit Registration System (NSEERS) di Amerika Serikat Era Obama - Adriana, Ida Ayu Mirah; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This study aims to describe policy changes made by the United States to stabilize its domestic situation. During the Bush administration the United States received a shocking attack from terrorist groups. Bush made NSEERS policy to secure his country and improve the image of the United States as a large and powerful country. But the NSEERS policy implemented by Bush had a significant economic downturn for the United States. So through the next Obama era, the United States terminated the NSEERS policy.This study uses the concept of Rational Actor Choice and Determinant in an effort to explain the NSEERS policy termination decision. By using quasi-qualitative writing methods the author concludes that the United States through Obama has calculated the termination of the NSEERS, the Obama administration prioritizes economic goals rather than emphasizing security interests or public opinion during the government era before that was Bush. Keywords : United States, Obama, Economy, NSEERS